The impact of brand ambassador values on consumer purchase decision in the Czech market - Jančíková, Tereza; Escobar Rios, Andrea; Bahles, Michael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the impact of three brand ambassador values—credibility, attractiveness, and relatability—on the purchasing decisions of consumers in the Czech market. The primary aim was to identify which of these values are most important for different demographic groups, specifically considering age and gender. Through a combination of theoretical analysis and a quantitative survey of Czech consumers, the research found that credibility is the most influential attribute overall, with younger consumers placing even greater emphasis on it than older consumers. Attractiveness was also found to be more important to younger respondents, likely due to their higher engagement with social media and digital marketing. Relatability was valued across all groups but did not show significant differences between demographics. The main conclusion is that age, rather than gender, significantly shapes consumer responses to brand ambassador values, suggesting that marketing strategies should be tailored more precisely to different age groups to maximize effectiveness.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses